2002
DOI: 10.1007/s00018-002-8437-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycosylation in protein antigenic properties

Abstract: Glycosylation of proteins is a common event and contributes to protein antigenic properties. Most data have been obtained from model studies on glycoprotens with well-defined structure or synthetic glycopeptides and their respective monoclonal antibodies. Antibodies raised against glycoprotein antigens may be specific for their carbohydrate units which are recognized irrespective of the protein carrier (carbohydrate epitopes), or in the context of the adjacent amino acid residues (glycopeptidic epitopes). Conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 74 publications
2
51
0
4
Order By: Relevance
“…In addition, the amino acid sequence of Pfs25 contains three putative asparagine N-linked glycosylation sites. Posttranslational modifications such as N-glycosylation have been known to play a crucial role in the folding, stability, and functional integrity of proteins (18,19). Glycosylation of proteins in Plasmodium has remained highly controversial (20), and a recent study has suggested formation of severely truncated N-glycan side chains due to the absence of glycosyltransferases required for precursor side chain generation (21).…”
mentioning
confidence: 99%
“…In addition, the amino acid sequence of Pfs25 contains three putative asparagine N-linked glycosylation sites. Posttranslational modifications such as N-glycosylation have been known to play a crucial role in the folding, stability, and functional integrity of proteins (18,19). Glycosylation of proteins in Plasmodium has remained highly controversial (20), and a recent study has suggested formation of severely truncated N-glycan side chains due to the absence of glycosyltransferases required for precursor side chain generation (21).…”
mentioning
confidence: 99%
“…Ascorbic acid has important functions, such as lymphocyte transformation, preventing oxidation of molecules used in the metabolic pathways, increasing chemotactic activity in neutrophils, collagen synthesis, hydrogen transport, regular growth and nucleic acid synthesis (Wang et al, 2003). The type of collagen which increased in fish exposed to ascorbic acid were identified as glycoproteins containing sialic acid groups (Lisowska, 2002;Yavuz, 2001). Dubey et al (2014) reported that Clarias batrachus -1 exposed to 0.45 µgl dimethoate increased the level of the hepatic glutamate oxaloacetate transaminase, glutamate pyrophosphate transaminase, acid phosphatase, and alkaline phosphatase enzymes were increased after 30 and 60 days compared to control fish, however protein content of the fish decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Великий вугле вод ний компо нент, експонований на зовнішньому боці клітинної мембрани, робить гліко форини го лов ними імунологічними детермінантами поверхні еритро цитів. У глікофоринах міс тяться детермінанти груп крові MN, Ss, Ge, рецептори, які взаємо діють з поверх нею бактерій, вірусів (вірус грипу, реовірус), паразитів (малярійний плазмо дій) [13,24,32,34,38,41,56,63]. Стан вуглеводного компонента глікофоринів є сигналом для розпізна вання старіючих або пошкоджених еритроцитів для по даль шого вида лення їх із кров'яного русла [8,17].…”
Section: характеристика ключових глікопротеїнів еритроцитів людиниunclassified